Virtual Reality Meets Non-invasive Brain Stimulation: Integrating Two Methods for Cognitive Rehabilitation of Mild Cognitive Impairment - Mancuso, Valentina; Stramba-Badiale, Chiara; Cavedoni, Silvia; Pedroli, Elisa; Cipresso, Pietro; Riva, Giuseppe (Frontiers in Neurology, 2020)
Mild cognitive impairment refers to a subtle, general cognitive decline with a detrimental impact on elderlies' independent living and quality of life. Without a timely diagnosis, this condition can evolve into dementia over time, hence the crucial need for early detection, prevention and rehabilitation. For this purpose, current neuropsychological interventions have been integrated with (i) virtual reality, which immerses the user in a controlled, ecological and safe environment (so far, both virtual reality-based cognitive and motor rehabilitation have revealed promising positive outcomes); and (ii) noninvasive brain stimulation, i.e. transcranial magnetic or electric brain stimulation, which has emerged as a promising cognitive treatment for mild cognitive impairment and Alzheimer's dementia. To date, these two methods have been employed separately; only a few studies (limited to motor rehabilitation) have suggested their integration. The present paper suggests to extend this integration to cognitive rehabilitation as well as to provide a multimodal stimulation that could enhance cognitive training, resulting in a more efficient rehabilitation.